2017
DOI: 10.1007/s13361-017-1636-9
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Chemical Mass Spectrometry: Verification and Extension of the Mobile Proton Model for Histidine

Abstract: The quantum chemical mass spectrometry for materials science (QCMS) method is used to verify the proposed mechanism for proton transfer - the Mobile Proton Model (MPM) - by histidine for ten XHS tripeptides, based on quantum chemical calculations at the DFT/B3LYP/6-311+G* level of theory. The fragmentations of the different intermediate structures in the MPM mechanism are studied within the QCMS framework, and the energetics of the proposed mechanism itself and those of the fragmentations of the intermediate s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 68 publications
0
16
0
1
Order By: Relevance
“…As the cleavage of the histidine amide bond leads to the formation of the b 2 ‐ion and requires a proton transfer from the initial protonation site to this amide bond, all the protonated species involved in this step should be considered. The most energy‐favorable protonation site of QHS, that is, the initial protonation site, is the imidazole ring of the histidine side chain 40 : protonation at the histidine amide oxygen atom is 47.01 kJ mol −1 less favorable, whereas protonation at the histidine amide nitrogen atom is 71.84 kJ mol −1 higher in energy (Figure 1). These energetics are consistent with the literature values and clearly show that, for QHS, amide oxygen protonation is energetically favored over amide nitrogen protonation 32 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As the cleavage of the histidine amide bond leads to the formation of the b 2 ‐ion and requires a proton transfer from the initial protonation site to this amide bond, all the protonated species involved in this step should be considered. The most energy‐favorable protonation site of QHS, that is, the initial protonation site, is the imidazole ring of the histidine side chain 40 : protonation at the histidine amide oxygen atom is 47.01 kJ mol −1 less favorable, whereas protonation at the histidine amide nitrogen atom is 71.84 kJ mol −1 higher in energy (Figure 1). These energetics are consistent with the literature values and clearly show that, for QHS, amide oxygen protonation is energetically favored over amide nitrogen protonation 32 …”
Section: Resultsmentioning
confidence: 99%
“…We intended to contribute to this field of research in a similar way, but the aim was to scrutinize the important effects of side‐chain reactive functions in the presence of the imidazole moiety in the formation of b 2 ‐ions 40 . We intentionally chose more complex tripeptides corresponding to X‐His‐Ser sequences, X = Asn, Asp, Gln, Glu, His, Pro, Lys, Ser, Trp, and Tyr, to evaluate the influence of ISC interactions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…From these energies, they try to predict not only the fragmentation pathways but also intensities. However, they showed that the estimation of intensities is in general difficult, as these also depend on specific measurement conditions (figure 8 in Cautereels et al) . Janesko et al also apply quantum chemical methods to simulate and understand mass spectra.…”
Section: Introductionmentioning
confidence: 99%
“…However, they showed that the estimation of intensities is in general difficult, as these also depend on specific measurement conditions (figure 8 in Cautereels et al 17 ). 18 Janesko et al 19 also apply quantum chemical methods to simulate and understand mass spectra. However, they do not aim to simulate an entire spectrum.…”
Section: Introductionmentioning
confidence: 99%